Naturally Occurring tRNAs With Non-canonical Structures - Krahn, Natalie; Fischer, Jonathan T.; Söll, Dieter (Frontiers in Microbiology, 2020)
Transfer RNA (tRNA) is the central molecule in genetically encoded protein synthesis. Most tRNA species were found to be very similar in structure: the well-known cloverleaf secondary structure and L-shaped tertiary structure. Furthermore, the length of the acceptor arm, T-arm, and anticodon arm were found to be closely conserved. Later research discovered naturally occurring, active tRNAs that did not fit the established ‘canonical’ tRNA structure. This review discusses the non-canonical structures of some well-characterized natural tRNA species and describes how these structures relate to their role in translation. Additionally, we highlight some newly discovered tRNAs in which the structure-function relationship is not yet fully understood.